Effect of Process Parameters on Shear Layer Thickness in Injection Molded Short-Glass Fiber Reinforced Polypropylene - Altan, M.; Demirci, M. (WALTER DE GRUYTER GMBH, 2018)
Controlling fiber orientation and fiber distribution in plastic injection of glass reinforced polymers is important due to the improvement of the properties of the material. Variation in shear layer thickness of fiber distribution affects the properties of the injection moldings. In this study, 30% glass fiber reinforced polypropylene was injected under various injection molding conditions in order to increase the shear layer thickness in which fiber orientation was parallel to the flow direction. The experimental study was carried out according to the Taguchi L9 orthogonal array. The mold temperature, nozzle temperature and injection rate were chosen as input parameters and the thickness of the shear layer was taken as output. Analysis of variance was also applied to observe the effectiveness of the process parameters on shear layer thickness. The shear layer thickness was measured over the images obtained by scanning electron microscopy. In order to investigate the dynamic mechanical behavior of the material depending on fiber distribution, dynamical mechanical analysis was applied. Storage modulus, loss modulus and tan delta values were obtained. It has been observed that higher mold temperature and nozzle temperature values increased shear layer thickness in injection molding of glass fiber reinforced polypropylene. It has been seen that 65% of increment in shear layer thickness induced approximately 50% of increment in storage modulus and loss modulus.
Keywords: FILLING STAGE; CARBON-FIBER; ORIENTATION; TENSILE; Engineering; Polymer Science